2013
DOI: 10.1371/journal.pone.0081853
|View full text |Cite
|
Sign up to set email alerts
|

32 species validation of a new Illumina paired-end approach for the development of microsatellites

Abstract: Development and optimization of novel species-specific microsatellites, or simple sequence repeats (SSRs) remains an important step for studies in ecology, evolution, and behavior. Numerous approaches exist for identifying new SSRs that vary widely in terms of both time and cost investments. A recent approach of using paired-end Illumina sequence data in conjunction with the bioinformatics pipeline, PAL_FINDER, has the potential to substantially reduce the cost and labor investment while also improving efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The power to detect differentiation and the accuracy of assignment tests are both directly related to the number of informative loci. To improve assignment tests results, we screened an additional 66 microsatellite loci and ultimately identified and optimized an additional 22 loci, 14 identified from screening the common bottlenose dolphin genome through Illumina 454 sequencing (see Lance et al 2013) and 8 optimized from loci previously identified in other cetacean species. See Text S1 in the Supplement for description of methods to identify and optimize these additional loci.…”
Section: Sampling Dna Extraction Microsatellite Genotypingmentioning
confidence: 99%
“…The power to detect differentiation and the accuracy of assignment tests are both directly related to the number of informative loci. To improve assignment tests results, we screened an additional 66 microsatellite loci and ultimately identified and optimized an additional 22 loci, 14 identified from screening the common bottlenose dolphin genome through Illumina 454 sequencing (see Lance et al 2013) and 8 optimized from loci previously identified in other cetacean species. See Text S1 in the Supplement for description of methods to identify and optimize these additional loci.…”
Section: Sampling Dna Extraction Microsatellite Genotypingmentioning
confidence: 99%
“…It inhabits mountain streams that can dry out in the summer months (Baumann & Gaufin, 1969). The data were generated by Lance et al (2013) for microsatellite marker development. The data were generated by Lance et al (2013) for microsatellite marker development.…”
mentioning
confidence: 99%
“…For mitochondrial genome assembly HiSeq data from the NCBI SRA database was used (Accession ID: SRR1145748). Additional information about DNA extraction and sequencing are provided in Lance et al (2013). Additional information about DNA extraction and sequencing are provided in Lance et al (2013).…”
mentioning
confidence: 99%
“…Although many recent studies have been published on microsatellite marker development in which such sequences are mined (e.g. Cardoso et al 2013;Lance et al 2013), most studies do not make use of the full potential of the sequencing data in combination with multiple genotypes to predict the most polymorphic microsatellite markers. To our knowledge, only the recent study by Hoffman and Nichols (2011) utilized a similar approach to our study to identify polymorphic microsatellite markers from 454 sequences of the Antarctic fur seal (Arctocephalus gazella).…”
Section: An Efficient Strategy For Polymorphic Marker Developmentmentioning
confidence: 99%